THE REPRESENTATION OF MALE’S AND FEMALE’S IDENTITY THROUGH THE ASSESSMENT OF SEMANTIC MEANINGS AND PRAGMATIC MEANINGS IN FASHION MAGAZINE - Ramanda, Rizki (LANTERN (Journal on English Language, Culture and Literature), 2013)
Magazine is one kind of printed media that is published periodically. Magazine has a lot of types based on its main contain and the target of reader. It can be divided as news magazine, teen’s magazine, male’s magazine and female’s magazine. Then, male’s and female’s magazines can be specified into fashion magazine. The articles in fashion magazine contain the style of clothes, shoes, bags, and also the interest scent of perfume. Male’s magazine and female’s magazine have the different submission in representing the identity between male and female. The purpose of this research explains the process to deliver the information about male’s and female’s identities in explicit or implicit way. The writer analyzes the submission of information in Da Man, Details, and Esquire magazines for describing the identity of male. Then, the writer uses Nylon, Vogue, Glamour, and Cosmopolitan magazines to identify the identity of female. The difference of language used and the submission of information between male and female are phenomena of language that are analyzed through the writer’s point of view by using some theories. The writer uses descriptive qualitative perspectives to determine the language usage between male and female in fashion magazines. The theory of explicature and implicature are used by the writer to analyze the submission of information in male’s and female’s articles through the objects of clothes, perfumes, and shoes. In the method of collecting data, the writer applies documentation method and note taking technique. From the data analysis, the writer concludes that the components of colors do not affect the appearance of male’s identity because the colors describe neutral colors. On the other side, female has close relation with the component of colors because female has her own colors, such as pink, gold, and fuchsia to represent the identity of female as a feminine person. Then, the submission of meaning in representing male’s and female’s identity can be categorized in two ways, such as in explicit or implicit way. Both of ways have the important role to determine the influence characteristics between male and female. The kind of implicature is often used to represent the identity of male and female because the information is presented indirectly and the writer should find the implied meaning in the sentence. Keywords: Explicature and Implicature Meaning, Fashion Magazine